First record of the genus Sergeya Ponomarenko, 2008 (Lepidoptera, Gelechiidae) from the Afrotropical and Oriental regions, with description of ten new species - Bidzilya, Oleksiy V.; Mey, Wolfram; Rajaei, Hossein (Zootaxa, 2024)
Genus Sergeya Ponomarenko, 2008 is recorded here for the first time from the Afrotropical and Oriental regions. Ten species are described as new: S. hackeri sp. nov. (Yemen), S. olei sp. nov. (Thailand), S. chuii sp. nov. (DR Congo), S. bunsoensis sp. nov. (Ghana), S. palescens sp. nov. (Uganda, South Africa), S. malawica sp. nov. (Malawi), S. korongotaji sp. nov. (Uganda), S. lobata sp. nov. (South Africa, Uganda, Ethiopia), S. davidi sp. nov. (Kenya), S. harambee sp. nov. (Kenya). The genus is redescribed, and its differences from most related Afrotropical genus Lanceopenna Janse, 1950, as well as Oriental Neolitinia Ponomarenko, Omelko & Omelko, 2021 and Parateleiopsis Ponomarenko, Omelko & Omelko, 2021 are discussed. Additionally, Lanceopenna prominula (Meyrick, 1913) (Aristotelia) is transferred from the genus Lanceopenna to Sergeya: S. prominula (Meyrick, 1913) comb. nov. and is recorded for the first time from Zimbabwe. All Afrotropical species of Sergeya are diagnosed, and an identification key to all species of the genus is provided. Wing pattern and genitalia of all species are illustrated. A lectotype is designated for Aristotelia prominula Meyrick, 1913. An updated check-list of species of Sergeya is provided.